THE ROLE OF CINEMATOGRAPHY IN THE FIELD OF TECHNOLOGY AND INFORMATION AS A MEDIA PROMOTION FOR BENGKULU PROVINCE TOURISM DEPARTMENT - Ardi Wijaya; Yovi Apridiansyah; Yulia Darnita; Irsyad Ahmad Fauzan; Thio Ragil Alfares; Muhammad Aksyah (Gayaku Publisher, 2023)
The Bengkulu Provincial Tourism Office (DISPARPROV BENGKULU) is a government agency engaged in the preservation and empowerment of tourism in Bengkulu Province, located on Jl. Captain Pierre Tendean No. KM 6.5, Kec. Gading Cempaka., Bengkulu City. This Community Service Program aims to describe and conduct training on the important role of cinematography for staff and contract employees at the Bengkulu Province Tourism Office as a means of promotional media. Linking digital cinematography with the development of multimedia as a form of information and communication technology. The purpose of carrying out this Community Service activity is to introduce and conduct direct training on cinematography as a promotional medium for staff employees and contract workers at the Bengkulu Provincial Tourism Office. This Community Service Activity uses a descriptive method with a qualitative approach. While the target audience is staff employees and honorary workers. Data collection uses qualitative methods. By holding Community Service activities through training in achieving the success of this program, it is by providing direct opportunities to employees of staff and temporary workers on how to edit videos and images as promotional media.